Sedimentology and stratigraphy - Nichols, Gary (Hoboken : Wiley, 2023)
Sedimentology and Stratigraphy introduces the reader to the subjects and provides tools for the interpretation of sediments and sedimentary rocks, covering the processes of formation, transport, and deposition of sediment and applying them to develop conceptual models for the full range of sedimentary environments, from deserts to deep seas and reefs to rivers. Different approaches to using stratigraphic principles to date and correlate strata are also considered to provide a comprehensive overview of all aspects of sedimentology and stratigraphy.
Includes bibliographical references and index.
Keywords: Sedimentation and deposition; Sedimentary environments; Depositional processes